Psychological burden, stressors and resources of social workers working with women and children who suffered extreme violence by the "Islamic state": a mixed method study - Binder, Annette; Nikendei, Christoph; Kindermann, David (Journal of psychosomatic research, 2020)
Objective - This explorative study aimed to determine the extent of psychological burden in social workers working with traumatized refugees. In addition, distressing and helpful factors determining the psychosocial burden were to be identified and described. - Methods - Cross-sectional, mixed method design using quantitative and qualitative methods. The quantitative part included the Perceived Stress Questionnaire (PSQ) and items to assess specific factors of the working-context. The qualitative part is based on 5 focus groupdiscussions and 16 individual interviews. Evaluation was carried out using qualitative content analysis (QCA) including cross-analysis along the subscales of the PSQ to organise the qualitative material. - Results - N = 54 social workers completed the questionnaire. High scores were found for all subscales of the PSQ. The distressing factor rated the highest was need of interpreters to communicate (M = 5.1, SD = 1.71), the helpful factor rated the highest was communication skills (M = 6.35, SD = 0.73). In the QCA, aspects of distressing and helpful factors were identified and further detailed. - Conclusion - According to the here presented study results, the psychological burdens of social workers working with refugees seem to be high. The impact of distressing factors such as working with interpreters and exposure to trauma content or PTSD symptoms might be reduced by offering specific education and supervision. The individual extent of psychological burden should be considered and (re-)evaluated on a regular basis as secondary prevention. Helpful factors like self-care, teamwork, networking and cooperation are evident and should be supported by implementing professional and psychological support.